Fixed-dose Combination of Dapagliflozin and Linagliptin in Individuals with Type 2 Diabetes Mellitus Inadequately Controlled on Metformin: A Randomized Double-blind Multicenter Trial - Kumthekar, Prashant; Upadhyay, Mihir R.; Tamma, Rajasekhara Reddy; Kranti, Vijay; Bhattacharya, Raja; Sharma, Prabhat Kumar; Barge, Vijaykumar Bhagwan; Revankar, Santosh; Ghatge, Shweta (Journal of diabetology, 2025)
Abstract Context: Combining dipeptidyl peptidase 4 inhibitors and sodium-glucose cotransporter-2 inhibitors in therapy could be beneficial for those with metformin intolerance or not achieving adequate control. Aims: To evaluate the efficacy, safety, and tolerability of a fixed-dose combination (FDC) of dapagliflozin plus linagliptin in patients with type 2 diabetes mellitus (T2DM) inadequately controlled on metformin. Settings and Design: It is a phase III, prospective, randomized, double-blind, multicenter study. Materials and Methods: Patients with T2DM, with a stable dose of metformin ≥1000 mg/day as monotherapy for at least 3 months before screening, with inadequate glycemic control at screening were randomly assigned to either arm A (dapagliflozin 10 mg + linagliptin 5 mg) or arm B (linagliptin 5 mg) in a 1:1 ratio. Statistical Analysis Used: The primary and secondary efficacy endpoint analyses were done using repeated measures analysis of covariance or a two-sample t test. All safety parameters were analyzed using a two-sample t test and descriptive statistics. Results: A total of 232 patients were randomized in arm A (n = 112) and arm B (n = 110). At week 16, arm A showed a significant mean reduction in glycated hemoglobin (HbA1c) than arm B (−1.35% vs. −0.92%; P≤0.0001). Similarly, the mean reductions in fasting plasma glucose (−26.13 mg/dL vs. −22.59 mg/dL; P = 0.0492), 2-h postprandial plasma glucose (−52.29 mg/dL vs. −30.35 mg/dL; P≤0.0001), and body weight (−1.32 kg vs. −0.42 kg; P≤0.0001) were significantly higher in arm A than in arm B. Arm A had a higher proportion of patients achieving HbA1c <7.0% (42.24% vs. 22.41%; P = 0.0012). Adverse events were comparable between study arms. Conclusions: The FDC of dapagliflozin and linagliptin was superior in terms of improvement in glycemic control and a higher proportion of patients achieving target HbA1c level, with both treatment arms being well-tolerated.